MENINGKATKAN KEMAMPUAN MENGGUNAKAN PECAHAN DALAM PEMECAHAN MASALAH MELALUI MEDIA PUZZLE BAGI ANAK BERKESULITAN BELAJAR - Joice Phunia Dame; Ardisal Ardisal; Marlina Marlina (Universitas Negeri Padang, 2014)
The research on the back by the fourth grade students in SDN 13 Pasar Remaja Sawahlunto, for proving puzzle. Media can improve the ability to compare two fractions for kids learning disabilities at 13 Pasar SDN Remaja. This This study used an experimental approach in the form of Single Subject Design (SSD) with a research design using ABA design. Media puzzle can enhance the ability to compare two fractions to fourth-grade children learning disabilities at SDN 13 Pasar Remaja. Kata Kunci: Anak berkesulitan belajar; Membandingkan dua pecahan; Media puzzle